Case Report: SLC52A2 variants cause Brown-Vialetto-Van Laere syndrome type 2, characterized by pure red cell aplastic anemia: clinical and genetic features of three Chinese children - Chen, Zhenzhen; Lai, Landi; Lu, Xiaomei; Zhong, Bomao; Peng, Qi; Liu, Ziqiang (Frontiers in Pediatrics, 2026)
ObjectiveTo report three Chinese pediatric cases of Brown-Vialetto-Van Laere syndrome type 2 (BVVLS2) presenting with pure red cell aplasia (PRCA) as the core manifestation, and to analyze their clinical features, molecular basis, and response to riboflavin therapy.MethodsWe conducted a retrospective analysis of three pediatric cases, integrating detailed clinical phenotyping with comprehensive genetic analysis (including whole-exome/targeted sequencing, Sanger validation, and ACMG-based variant interpretation). To elucidate genotype-phenotype correlations, we interpreted these findings in the context of a literature review.ResultsAll three patients carried compound heterozygous variants in the SLC52A2 gene. Each exhibited early-onset PRCA (onset age: 2 days to 6 months; hemoglobin: 29–67 g/L) and progressive neurodegeneration, including motor regression, axonal peripheral neuropathy, and sensorineural hearing loss. Riboflavin supplementation led to normalization of hemoglobin levels within four weeks and marked improvement in neurological function.ConclusionThis case series provides detailed longitudinal data on riboflavin-responsive PRCA as a core presenting feature of BVVLS2 and reports rare SLC52A2 variants in the Chinese population. Early riboflavin treatment effectively reversed anemia and partially improved neurological deficits, which may inform a new diagnostic and therapeutic approach for unexplained PRCA accompanied by neurodegenerative features.